Pengaruh Intellectual Capital dan Good Corporate Governance terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Yolanda Fasya; Dinar Riftiasari; Achmad Ridwan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Company value represents investors' views on a firm's performance and potential future opportunities. This research seeks to offer empirical proof regarding the impact of Intellectual Capital and Good Corporate Governance on company value, using financial performance as an Intervening variable. The subjects of the study are financial sector firms listed on the Indonesia Stock Exchange (IDX) during the period of 2020 to 2024. This research employs a quantitative approach with purposive sampling, encompassing 9 firms from the financial sector. The methods of data analysis employed consist of descriptive analysis, path analysis, tests for classical assumptions, coefficient of determination (R²), partial t-test, simultaneous F-test, and Sobel test utilizing SPSS 26. The findings indicate that Intellectual Capital has a notable negative influence on company value, whereas Good Corporate Governance does not have a significant impact. Intellectual Capital and Good Corporate Governance both positively and significantly influence financial performance. Nonetheless, financial performance does not greatly impact firm value. At the same time, Intellectual Capital, Good Corporate Governance, and financial performance have a substantial impact on the value of a firm. The Sobel test indicates that financial performance does not act as a mediator between Intellectual Capital, Good Corporate Governance, and firm value